The Construction of the Contemporary Poetic Canon between Spain and Portugal. The Anthology of Eugénio de Andrade for O Comércio do Porto in the Mid-20th Century (BEOIBERÍSTICA - Journal of Iberian, Latin American and Comparative Studies (ISSN: 2560-4163 Online), 2018)
Throughout the twentieth century the various contacts and mutual reception between the poets of Spain and Portugal were the result of particular initiatives. Despite the importance and relative abundance of these confluences, a fluid and constant dialogue was never established on either side of the border. Perhaps this explains the scarce presence of poetic anthologies that picked up over the years the lyrical current of the neighboring country during most of the twentieth century. The anthology devised by Eugénio de Andrade in 1957 as commissioned by the editor Costa Barreto for the newspaper O Comércio do Porto and his monograph on Spanish poetry published in installments between December 1957 and February 1958 was in this sense the starting point for a series of anthologies that would appear from then on, thus enabling a more fluid reading of the Spanish poetic panorama in Portugal. This article aims to highlight the important role played by this mid-century anthology, analyzing its gestation, its composition process and some avatars of its intrahistory as the important role played by the Spanish poet Rafael Morales, a true intermediary between the anthologist and the selected poets. In conclusion, we must clearly highlight the important place occupied by this monograph of O Comércio do Porto in the complex and busy poetic dialogue maintained between Spain and Portugal throughout the past century.Key words: reception of Spanish poetry in Portugal, Eugénio de Andrade, literary canon, Iberian comparativism.